Clinical profile and immediate outcomes in neonates born to SARS-CoV-2 positive mothers at a tertiary care centre - Shreya Adavalath; K. Shreedhara Avabratha (Al Ameen Medical College, 2023)
Introduction: There is a scarcity of clinical data on the clinical profile of neonates born to COVID positive mothers as well as their immediate outcomes, especially in the Indian context. We aimed to describe the clinical profile and immediate outcomes of neonates born to SARS-CoV-2 positive mothers. Methods: This was a retrospective, chart based observational study conducted in the Neonatal Intensive Care Unit and post-natal wards at a tertiary care centre in Mangalore, Karnataka. All neonates born to women with SARS-CoV-2 infection within two weeks prior to or two days after delivery were included in the study. Data regarding epidemiologic, demographic, clinical features and laboratory tests in neonates born to covid positive mothers were recorded. Data was analysed using descriptive statistics and outcomes expressed as frequency, proportions, percentages and chi square test. Results: From April 2020 to September 2021, 99 babies born to covid positive mothers for were included. 31(32%) neonates were symptomatic and 66(68%) were asymptomatic. Out of the 99 neonates, 84 of the neonates were tested. 81(81.8%) were COVID negative. 3(3.6%) were tested positiveby quantitative RT PCR done within 72 hours of life. All the positive neonates were symptomatic and required respiratory support. Infected neonates had no statistically significant difference with noninfected. Conclusions: Covid positivity among neonates born to covid positive mothers was low and majority remained asymptomatic and overall neonates did well.